Developing Resilient Learners: The Contribution of Counseling to Student Motivation and Achievement - Igang, Fidellio Widhi Prasetyo; Soetjiningsih, Christiana Hari (Guidance and Counseling Study Program, Pattimura University, 2024)
This study investigates the relationship between learning motivation and academic self-efficacy among undergraduate psychology students from the 2020 cohort at Universitas Kristen Satya Wacana, focusing on those with a GPA of 3.00 or higher. Utilizing a quantitative correlational design, data was collected via a Google Form questionnaire distributed through WhatsApp from October 29, 2023, to April 24, 2024. Despite challenges in data collection, the study revealed that the majority of participants exhibited low levels of both learning motivation and academic self-efficacy. Descriptive statistics showed a mean learning motivation score of 37.07 and an academic self-efficacy score of 86.83. The correlation analysis indicated a significant positive relationship (r = 0.590, p < 0.05) between learning motivation and academic self-efficacy, suggesting that higher learning motivation corresponds to higher academic self-efficacy and vice versa. The findings emphasize the importance of enhancing both intrinsic and extrinsic motivation, building mastery experiences, and ensuring students' physical and emotional well-being to foster better academic outcomes. These insights have crucial implications for counseling and guidance services, advocating for targeted interventions to improve learning motivation and academic self-efficacy among students.